Basic solutions for a program system for dynamic systems simulation - Timofeev, Alexander (Studia Informatica. System and information technology, 2006)
The article presents basic solutions of the Amethyst program system. The system generates interactive applications for simulating complex dynamic systems. The method of presenting the information about the state of the simulated objects and method of calculating the component state are proposed. Method of decentralized processing the signal delays and filtering is discussed. Method of analog objects simulating is proposed. The article presents examples of projects produced for C++ Builder, Visual C++ and Visual Basic 2005 environment projects. The executable times of simulation are compared for the above mentioned environment applications.